Emerging challenges of Garda tourism: culture, sustainability and new technologies - Corradi, Valerio (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2019)
With over 24 million annual presences, Lake Garda is one of the main Italian tourist destinations. In recent years, the tourist demand that addresses this area, which insists on three regions (Lombardy, Veneto, Trentino A.A.), has shown important signs of change. New sensitivities are emerging which need to be understood also in relation to the local offer model and the type of territorial development pursued in the last as well as its social, economic and environmental impact. A research conducted by a team from the Catholic University of Brescia, supported among others by the Province of Brescia, the Community of Garda and the Lake GardaLombardy Consortium, investigated (through a sample of 800 tourists) the most recent transformations in tourism Garda by recording the behaviors implemented during the holiday (preferences, orientations, satisfaction, use of new technologies, etc.) and emerging sensitivities (contact with nature, search for comfort, etc.).